2009
DOI: 10.2169/internalmedicine.48.1811
|View full text |Cite
|
Sign up to set email alerts
|

Cladosporium Species-Related Hypersensitivity Pneumonitis in Household Environments

Abstract: Home-related chronic hypersensitivity pneumonitis (HP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Cladosporium spp. is the common and widespread fungi on land and in air [36, 37]. Although there are no publications regarding its ability of producing toxin, they do produce odours likely relating to some volatile organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Cladosporium spp. is the common and widespread fungi on land and in air [36, 37]. Although there are no publications regarding its ability of producing toxin, they do produce odours likely relating to some volatile organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…A significant relationship was found between the reduction in lung function and airborne mold concentrations (Dahlqvist et al 1992). Respiratory symptoms, febrile episodes, allergic diseases such as hypersensitivity pneumonitis, and asthma due to bioaerosol exposure have been documented among workers employed in waste industry (Chiba et al 2009;Poulsen et al 1995). It was also found that not only viable, but also non-viable bioaerosol particles are capable of causing adverse health effects (Adhikari et al 2009;Gorny et al 2002;Robbins et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…There are many ILDs with different etiologies and histological manifestations, and histological manifestation does not correspond to etiology according to a one-to-one relation (Scott et al 1990;Baumgartner 2000;Miyake 2005). In addition, HP cases indistinguishable from IIPs have recently been recognized (Chiba et al 2009). Thus, a diagnosis system for the etiological factors is needed which involves lower invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported a patient with chronic HP caused by Cladosporium species that developed in a household environment, but not in specific environments (Chiba et al 2009). Although several coincidences helped us to reach a diagnosis of HP in this case after several years of follow up, a large number of patients with HP can be misdiagnosed as IIPs.…”
mentioning
confidence: 98%